2018
DOI: 10.1038/s41380-018-0277-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influence on cognitive development between childhood and adulthood

Abstract: Successful cognitive development between childhood and adulthood has important consequences for future mental and physical wellbeing, as well as occupational and financial success. Therefore, delineating the genetic influences underlying changes in cognitive abilities during this developmental period will provide important insights into the biological mechanisms that govern both typical and atypical maturation. Using data from the Philadelphia Neurodevelopmental Cohort (PNC), a large population-based sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 65 publications
10
31
1
Order By: Relevance
“…The vector of g loadings is the g loadings for the 10 subtests found to be MI for African and European-Americans. The vector of heritability is the average of the African-and European-American heritabilities reported by Mollon et al [65]. The vectors of group differences were: (1) the correlation with European ancestry (for the combined sample), (2) the correlation with MTAG 10K eduPGS for the European-American sample, (3) the correlation with MTAG 10k eduPGS for the monoracial African-American sample, and (4) the African-/European-American mean group differences.…”
Section: The Spearman-jensen Hypothesismentioning
confidence: 99%
“…The vector of g loadings is the g loadings for the 10 subtests found to be MI for African and European-Americans. The vector of heritability is the average of the African-and European-American heritabilities reported by Mollon et al [65]. The vectors of group differences were: (1) the correlation with European ancestry (for the combined sample), (2) the correlation with MTAG 10K eduPGS for the European-American sample, (3) the correlation with MTAG 10k eduPGS for the monoracial African-American sample, and (4) the African-/European-American mean group differences.…”
Section: The Spearman-jensen Hypothesismentioning
confidence: 99%
“…The battery also included the reading subtest of the Wide Range Achievement Test (WRAT), a measure of general verbal knowledge. As in our prior work [23], we derived a general composite score (g) as the first component of principal component analysis (PCA) of accuracy scores. We also derived a general composite score for speed (gs) as the first component of PCA of reaction times.…”
Section: Cognitive Assessmentmentioning
confidence: 99%
“…Early life psychopathology is also underpinned by genes, with evidence of substantial genetic effects on childhood and adolescent psychopathology [9,10], as well as specific psychotic [11,12], externalizing [13][14][15], internalizing [16], and anxiety/depression symptoms [17][18][19][20][21]. Since cognition in early life is also influenced by genes [22,23], recent studies have examined whether there is a genetic component to cognitive correlates of early life psychopathology. Evidence from twin and family studies shows genetic overlap between psychopathology and cognitive ability [24], psychopathology and executive functions [25], ADHD and IQ [26], ADHD and executive functions [27,28], and inattention and attention regulation [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, different environmental factors in childhood may reduce the effect of exposure to abnormal glucose tolerance levels in utero 50 . Another possible explanation is based on the heritability of cognitive development including attention and memory 51,52 . Studies showed that the heritability of cognition depended on the developmental period (it increases from around 40% in early childhood to over 80% in elders), reflecting increasing active gene‐environment correlation as positive feedback loops (eg brighter children seek more cognitive stimulation) 53 .…”
Section: Commentmentioning
confidence: 99%